Calcium carbonate capsules production with an automatic encapsulator in the galenic laboratory of the hospital pharmacy of ASL CN2. Issue 2 (12th March 2012) - Mittone, E.; Antonuccio, G.; Infante, L.; Recalenda, V.; Riella, F.; Gallarate, M.
Abstract : Background: Calcium carbonate capsules is a drug used in the hospitals with nephrology-department but it doesn't exist like industrial drug in Italy. Normally is acquired by external companies like food-integrator or produced in galenic laboratories with manual encapsulators. In this paper a survey on a recent study to optimise the use of the automatic-capper ZANASI-LZ-64-Tecnofarma (ACZT) is presented. Galenic laboratory of ASLCN2 is equipped of ACZT. Purpose: Formulation of apt calcium carbonate mixture to ACZT; Realisation of procedures for the use of ACZT and its calibration; pharmacoeconomic study. Materials and methods: In order to choose the optimal mixture a comparison between manual-mixing in mortar and an automatic-mixing with rotary-body mixer is taken into account. A sliding-test FUXII on different mixtures has also been performed. Finally the samples obtained varying the mechanical parameters of ACTZ were tested (uniformity-mass-test FUXII) to obtain 500 mg capsules. A pharmacoeconomical study to compare internal production costs and external provisioning costs is also presented. Results: In the experimental conditions manual-mixing is comparable and preferable to the automatic-mixing and can avoid dangers of powders sequestration for this purpose a new mortar mixing powders procedure is elaborated. No mixtures obtained with calcium carbonate glidants and lubricants has entered in the parameters for fluency because the angle of rest is higher than 35°; The authors have chosen the light calcium carbonate thanks to its angle of 33°. An update of the standard laboratory procedures with the operating instruction of ACZT, extraordinary-ordinary maintenance, extraordinary-ordinary cleansing has been done. Thanks to that is possible to reduce the cost of the produced capsules, of 1.491€. Conclusions: ACZT is an uncommon technology for galenic laboratory and has huge potentialities. The production of the calcium carbonate capsules could satisfy the requirements of Piedmont hospitals for orphan drug production.